2017
DOI: 10.1186/s40795-017-0205-8
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast among 8-9 year old children is associated with teacher-reported but not objectively measured academic performance two years later

Abstract: Background: Skipping breakfast, habitually and when experimentally manipulated, has been linked in the shortterm to poorer academic performance in children. Little is known about the longer-term effects. This study examined whether skipping breakfast at aged 8-9 years predicted poorer academic performance and classroom behavior 2 years later. Methods: The Longitudinal Study of Australian Children (LSAC) collected data during 2008 (aged 8-9 years) and 2010 (aged 10-11 years). Breakfast consumption was reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The provision of breakfast at school is designed explicitly to address the negative consequences of arriving at school hungry and support the health and well-being of children. As has been found in previous studies, adult participants identified improved concentration, classroom behavior, and academic outcomes of students who attended (Smith, Blizzard, et al, 2017). However, this study found that children did not eat breakfast at home for a variety of reasons, not all of them related to poverty or food insecurity.…”
Section: Discussionsupporting
confidence: 86%
“…The provision of breakfast at school is designed explicitly to address the negative consequences of arriving at school hungry and support the health and well-being of children. As has been found in previous studies, adult participants identified improved concentration, classroom behavior, and academic outcomes of students who attended (Smith, Blizzard, et al, 2017). However, this study found that children did not eat breakfast at home for a variety of reasons, not all of them related to poverty or food insecurity.…”
Section: Discussionsupporting
confidence: 86%
“…Children who regularly eat breakfast perform better academically than children who skip breakfast [19,20]. Children who consume a nutritious breakfast score higher in literacy tests than those who skip breakfast [21].…”
Section: Introductionmentioning
confidence: 99%
“…Children who didn’t skip their breakfast were 2 times more likely to have good academic score. The longitudinal study conducted among Australian children also revealed that over all academic achievement were higher in breakfast non-skippers than breakfast skippers [19]. A cross sectional study conducted in southern Ethiopia also shown that habit of skipping breakfast affected the cognitive performance of early adolescents [20].…”
Section: Discussionmentioning
confidence: 99%